MÉTODO DE MPPT HÍBRIDO PARA CONTROLE DE UM MICROGERADOR HIDROCINÉTICO DE CANAIS ABERTOS EM​ MODO CONECTADO À REDE ELÉTRICA - EDIGAR NUNES DE SIQUEIRA JÚNIOR (2024)
The search for cleaner and more sustainable sources has become a global trend and, in a way, has favored the development of technologies which were previously treated only conceptually. Hydrokinetic energy conversion, for instance, has been gaining notoriety among renewable energy sources due to its reasonable predictability and reduced environmental impact. In this context, this dissertation proposes the development of a maximum power point tracking (MPPT) algorithm for controlling an open-channel hydrokinetic microgenerator in grid-connected mode. The strategy, which combines the flexibility of the traditional “perturb and observe” method with the stability of the V–P (voltage–power) curve, aims to maximize energy capture and ensure operational reliability. The 10-kW unit consists of a current turbine, a permanent magnet synchronous generator, an uncontrolled full-bridge rectifier, and a three-phase voltage source inverter. In addition to MPPT subsystem, the control stage is composed of a DC bus voltage regulator, output current compensators, phase-locked loops (PLLs), a slip mode frequency shift (SMS) islanding detector and a sinusoidal pulse width modulation (SPWM) device. Using a simulation-based approach on MATLAB/Simulink® platform, the technique has been validated based on the model’s response under varying flow conditions, achieving a tracking efficiency of 96.21%.